Assessment of the current practice of antibiotic skin testing in a tertiary Hospital in United Arab Emirates - AbdulAzeez, Shemeena; Al Tajir, Ghada Khalil; Sulieman, Hana (The Journal of Infection in Developing Countries, 2011)
Introduction: Skin testing can be a useful diagnostic tool to identify patients who are allergic to penicillin. Procedures for skin testing in the United Arab Emirates have not been standardized. The aim of this study was to examine the current practice of antibiotic skin testing in a tertiary hospital in the United Arab Emirates (UAE). Methodology: This was a prospective cross-sectional study conducted in Al Qassimi Hospital, in which the medical records of all patients who were prescribed antibiotics over an eight-week period were screened to evaluate patients' history, indication for performing the test, results, and documentation of findings. Results: During the study period 357 patients received parenteral antibiotics, of which 238 had one skin test, 21 had two skin tests, and one patient had four skin tests. Skin testing was performed without regard for patient history. Documentation of both positive and negative results was poor. There was no standard technique for skin testing used within the institution, and significant variations were noted between wards. In most cases the techniques used deviated from recommended procedures in the medical literature. Conclusions: Standardized guidelines for antibiotic skin testing should be established and implemented as soon as possible using recommended international guidelines.